Tinjauan Ikonografi pada Lukisan “Hidup ini Indah Apapun Keadaannya” - Tobias Warbung (Bina Nusantara University, 2015)
Painting ‘Hidup Ini Indah Apapun Keadaannya’ was made to commemorate the 5.9 magnitude earthquake occurred in Yogyakarta. This painting shows an unusual visual and illustration with depth of meaning. The relationship between symbols, shapes, and colors could give unique impression to the person who saw it. It became interesting to examine this painting using iconography method. This article examined relevant dimensions existing in the portrait, such as: theological, ethical, cultural anthropology, and psychology. These dimensions are perceived to be able to convey the message and profound meaning to the people who look at the painting. Through this painting, art was believed to have strength to create society to be better.